(Dis)fluentnost i proizvodnja govora - Horga, Damir (Slavistična revija, 2012)
The speaker's goal is to produce ideal speech, which is skillfully planned, grammatically correct, fluently executed, and communicatively appropriate. However, due to his/her biological nature and physiological features and communication conditions in which people produce speech, this speech can become dysfluent, thus indicating speech production difficulties. The complexity of speech production and (dys)fluency is explained by various models of speech production and the research looks at public (formal speech) and commercial (informal speech) radio speech.
Keywords: fonetika; formal speech; formalni govor; govorno dejanje; informal speech; izgovorna fonetika; neformalni govor; phonetics; radijski govor; radio speech; speech production